The Impact of Credit Policy Environment on Agricultural Output in Nigeria - Ini-mfon Vincent Patrick; Veronica Sebastin Nkanta; Edet Jouhua Udoh; Sunday Brownson Akpan (Research in Agricultural Sciences)
The growth of the agriculture sector is a key factor in the survival of the Nigerian economy. However, the production and productivity of this sector have been lower than expected recently. The country is now a net importer of some crops that were previously produced in large quantities. Hence, with the aim to identify factors that influence the sector, the study specifically establishes the relationship between the agricultural sector growth proxy by the agricultural production index and the credit policy variables in Nigeria. The research utilized the flexible autoregressive distributed lag (ARDL) approach to determine the presence of co-integration. The estimated long-run and short-run models demonstrated the best, most efficient, and unbiasedness qualities. The findings revealed that loans from commercial banks and the Agricultural Credit Guarantee Scheme Fund (ACGSF) have a significant positive impact on the agricultural sector's growth in the long run. Conversely, the long-run agricultural growth exhibited a negative relationship with the domestic credit to the private sector and lending interest rate. This finding underscores the importance of boosting commercial bank loans to the agricultural sector and increasing credit volume from the Agricultural Credit Guarantee Scheme Fund. Furthermore, it highlights the necessity of introducing more financial incentives to attract domestic private investments and lowering the lending interest rate on agricultural credit within the country.